FIBCD1 is an endocytic GAG receptor associated with a novel neurodevelopmental disorder - Christopher W Fell; Astrid Hagelkruys; Ana Cicvaric; Marion Horrer; Lucy Liu; Joshua Shing Shun Li; Johannes Stadlmann; Anton A Polyansky; Stefan Mereiter; Miguel Angel Tejada; Tomislav Kokotović; Venkat Swaroop Achuta; et al. (EMBO Molecular Medicine)
Abstract Whole‐exome sequencing of two patients with idiopathic complex neurodevelopmental disorder (NDD) identified biallelic variants of unknown significance within FIBCD1, encoding an endocytic acetyl group‐binding transmembrane receptor with no known function in the central nervous system. We found that FIBCD1 preferentially binds and endocytoses glycosaminoglycan (GAG) chondroitin sulphate‐4S (CS‐4S) and regulates GAG content of the brain extracellular matrix (ECM). In silico molecular simulation studies and GAG binding analyses of patient variants determined that such variants are loss‐of‐function by disrupting FIBCD1‐CS‐4S association. Gene knockdown in flies resulted in morphological disruption of the neuromuscular junction and motor‐related behavioural deficits. In humans and mice, FIBCD1 is expressed in discrete brain regions, including the hippocampus. Fibcd1 KO mice exhibited normal hippocampal neuronal morphology but impaired hippocampal‐dependent learning. Further, hippocampal synaptic remodelling in acute slices from Fibcd1 KO mice was deficient but restored upon enzymatically modulating the ECM. Together, we identified FIBCD1 as an endocytic receptor for GAGs in the brain ECM and a novel gene associated with an NDD, revealing a critical role in nervous system structure, function and plasticity.